Resilience Across Developmental Transitions: A Systematic Literature Review from Adolescence to Adulthood - Titin Kholisna; Sri Handayani (CV Rena Cipta Mandiri, 2026)
The aims study is to systematically review the literature on resilience across developmental transitions and to develop an integrative framework. This study employed a systematic literature review approach following PRISMA 2020 guidelines. Literature was collected from Scopus, Web of Science, PubMed, and Google Scholar within the publication period of 2015–2025. A total of 842 records were identified, and 28 articles met the inclusion criteria for final analysis.The results identified six main themes: resilience as a longitudinal developmental process, the interaction of risk and protective factors, psychological mechanisms with emphasis on emotional intelligence, neurobiological dimensions of resilience, effectiveness of resilience-based interventions, and the role of social support and identity in emerging adulthood. These findings indicate that resilience is a dynamic adaptive system shaped by the interaction of multidimensional factors over time.This study contributes to the development of a biopsychosocial framework of resilience and provides practical implications for designing resilience-based interventions among adolescents and emerging adults.